PENERAPAN TARGET COSTING DALAM UPAYA EFISIENSI BIAYA PRODUKSI PADA USAHA “SALA LAUAK” KELURAHAN PURUS-KOTA PADANG - Mike Kusuma Dewi; Elsa Meirina; Laynita Sari; Renil Septiano; Lisa Amelia Herman (LPPM Universitas Bina Bangsa, 2023)
The small and medium business sector (UMKM) is an important pillar in the Indonesian economy. There should be no doubt about its existence, considering that this sector absorbs a lot of labor which has proven to be able to survive in the midst of the storm of the economic crisis and become the driving force of the economy. Currently, UMKM are in a trend that positive with the number continuing to increase every year. This positive trend will have a good impact on the Indonesian economy. One of the business actors that dominates the most is the culinary sector. The culinary delights that will be used as material for this service are sala lauak snacks. In this service activity, we from the team provide education about the application of simple target costing to business actors which will be linked to the turnover generated by producers in 1 day. The application of target costing is based on the difference between the target cost per unit of production and the desired profit margin from the product selling price. Based on this, producers are expected to be able to generate maximum profits and further improve the quality standards of the products they produce